2019
DOI: 10.24198/kultivasi.v18i2.22184
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh dosis kascing dan bioaktivator terhadap pertumbuhan dan hasil tanaman sawi (Brassica juncea L.) yang dibudidayakan secara organik

Abstract: Sari. Peningkatan produktivitas sawi (Brassica juncea L.) dapat dilakukan secara organik. Tujuan penelitian ini untuk mengetahui pengaruh dosis kascing dan penggunaan bioaktivator terhadap pertumbuhan dan hasil tanaman sawi. Rancangan yang digunakan adalah Rancangan Acak Kelompok (RAK), terdiri atas sembilan kombinasi perlakuan dan diulang empat kali, masing-masing kombinasi perlakuan adalah: tanpa kascing dan tanpa bioaktivator; kascing 5 ton/ha dan tanpa bioaktivator; kascing 5 ton/ha dan bioaktivator 4 mL/L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 1 publication
1
6
0
3
Order By: Relevance
“…Research whose results are in line with this study, among others, Wahyudin and Irwan (2019) reported that vermicompost fertilizer treatment was able to increase the number of plant leaves. In addition, the application of vermicompost can also increase plant height, wet weight and dry weight of mustard plants.…”
Section: Long Bean Leaf Numbersupporting
confidence: 91%
“…Research whose results are in line with this study, among others, Wahyudin and Irwan (2019) reported that vermicompost fertilizer treatment was able to increase the number of plant leaves. In addition, the application of vermicompost can also increase plant height, wet weight and dry weight of mustard plants.…”
Section: Long Bean Leaf Numbersupporting
confidence: 91%
“…The extensive root system of a plant is essential for its growth, as it stores water and nutrients from the soil for later use in the plant's metabolism. In other words, roots are one of the organs of the plant that help plants grow [19]. If the roots are good, then the growth of other plant parts will develop well too, because the roots can absorb the nutrients plants need.…”
Section: Onion Plant Growthmentioning
confidence: 99%
“…Laju fotosintesis meningkat dapat menyebabkan sintesis karbohidrat juga meningkat. Peningkatan karbohidrat yang disebabkan oleh laju fotosintesis, meningkatkan pertumbuhan vegetatif tanaman termasuk pertumbuhan tinggi tanaman dan pembentukan daun (Wahyudin, 2005). Jika sintesis karbohidrat meningkat, maka kadar gula yang terdapat dalam karbohidrat dari hasil fotosintesis akan meningkat pula.…”
Section: Kadar Gulaunclassified